Paying Taxes 2015 : The Global Picture - World Bank Group; PwC (World Bank, Washington, DC, 2015)
This is the tenth year that the paying taxes indicator has been part of the World Bank Doing Business project. The journey over the period of the study has been an eventful and interesting one and the economic backdrop continues to present a challenging environment for governments as they consider their future fiscal policies. Globalization, the march of technological change, changing demographic patterns and the persistent challenges that continue around climate change and the environment all come together to generate a turbulent mix of issues which have a significant impact on fiscal policy and the associated tax systems. Against this backdrop, this year the Organization for Economic Co-operation and Development (OECD) has put forward proposals for changing the international tax rules to modernize them for today s globalized business and to address concerns over base erosion and profit shifting (BEPS). It is apparent that these proposals are already changing the way some tax authorities apply existing rules, leading to new and increased uncertainty for business, at least in the short term. Alongside all of this however there are two simple, mutually supportive objectives for governments; to ensure that there are sufficient public revenues for the future, to lay a foundation for sustained improvements in productivity, while at the same time incentivising investment and economic growth. This year the authors have also focused more on the compliance aspects of the information that authors collect through the study. Stable tax systems and strong tax administrations are important for businesses, helping them to operate in an environment where the tax treatment of transactions is predictable, and where governments operate transparently. The paying taxes study provides an unrivalled global database which supports an ongoing research program.